A prospective observational cohort study in primary care practices to identify factors associated with treatment failure in Staphylococcus aureus skin and soft tissue infections. Issue 1 (December 2016) - Lee, Grace; Hall, Ronald; Boyd, Natalie; Dallas, Steven; Du, Liem; Treviño, Lucina; Treviño, Sylvia; Retzloff, Chad; Lawson, Kenneth; Wilson, James; Olsen, Randall; Wang, Yufeng; et al.
Abstract Background The incidence of outpatient visits for skin and soft tissue infections (SSTIs) has substantially increased over the last decade. The emergence of community-associated methicillin-resistantStaphylococcus aureus (CA-MRSA) has made the management ofS. aureus SSTIs complex and challenging. The objective of this study was to identify risk factors contributing to treatment failures associated with community-associatedS. aureus skin and soft tissue infections SSTIs. Methods This was a prospective, observational study among 14 primary care clinics within the South Texas Ambulatory Research Network. The primary outcome was treatment failure within 90 days of the initial visit. Univariate associations between the explanatory variables and treatment failure were examined. A generalized linear mixed-effect model was developed to identify independent risk factors associated with treatment failure. Results Overall, 21% (22/106) patients withS. aureus SSTIs experienced treatment failure. The occurrence of treatment failure was similar among patients with methicillin-resistantS. aureus and those with methicillin-susceptibleS. aureus SSTIs (19 vs. 24%;p  = 0.70). Independent predictors of treatment failure among cases withS. aureus SSTIs was a duration of infection of ≥7 days prior to initial visit [aOR, 6.02 (95% CI 1.74–19.61)] and a lesion diameter size ≥5 cm [5.25 (1.58–17.20)]. Conclusions Predictors for treatment failure included a duration of infection for ≥7 days prior to the initial visit and a wound diameter of ≥5 cm. A heightened awareness of these risk factors could help direct targeted interventions in high-risk populations.